Economic Impacts of West Asia Conflicts: A Comprehensive Analysis - Dr. P. Govindaraj; Dr V. Murugesh (The Bioscan, 2026)
The West Asian region, often referred to as the Middle East, has been at the epicentre of geopolitical turbulence for decades. This paper examines the multidimensional economic consequences of ongoing and recent conflicts in West Asia, with a focus on their regional and global ramifications. Drawing on empirical data and existing literature, this study analyses the impact on energy markets, international trade routes, foreign direct investment (FDI), food security, inflation, and reconstruction costs. The findings reveal that West Asian conflicts function as systemic economic shock transmitters, with consequences that extend far beyond the immediate conflict zones. This paper concludes with policy recommendations for mitigating economic disruptions arising from regional instability.